Tarian Saba [ (Jabatan Muzium dan Antikuiti, 2001)
Documentary on saba dance. It consists of dance movements and songs, presented on special occasions based on beliefs in invisible powers. The dance has been performed in Kuala Jengai, Dungun for 150 years. It was introduced by a woman bomoh (shaman) for healing purposes. It is usually performed in a special area inside a house. The saba tree (Cycas spp.) became the most important object in this performance, which has a cast of three main characters: Abang Peduang, the sick person, and a deity